KEADILAN ORGANISASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PERAWAT RAWAT INAP - Susilawati, Sinta; Iva Prestiana, Novita Dian (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2017)
This study aims to determine the effect of organizational justice and quality of work life on organizational citizenship behavior on nurses at Karya Husada Hospita Cikampekl. This research will use quantitative method with research design using regression analysis. Subjects in this study were nurses inpatient at Karya Husada Hospital Cikampek amounted to 85 people consisting of 29 male and 56 female gender. This research uses organizational fairness scale with Alpha Cronbach value 0,942, work life quality scale with reliability value Aplha Cronbach 0,955 and scale organizational citizenship behavior with value of Aplha Cronbach 0,947. Data analysis technique use regression analysis. This study found that there is an influence between organizational Justice and quality of work life on organizational citizenship behavior